Methodological features of teaching toxicological chemistry in higher educational institutions of Ukraine - Fedotov, S. O.; Федотов, Сергій Олегович (Запорізький державний медичний університет, 2023)
Today, the training of pharmaceutical personnel as a chemist-toxicologist is based on a paradigm. The new educational standard requires the ability and willingness of a modern specialist to create conditions for certain activities and to perform the specified work in accordance with the state standard and legislation of Ukraine [4]. The goal of the work. Highlight the methodological features of teaching toxicological chemistry in higher educational institutions taking into account the requirements of the Bologna Declaration, because the training of specialists of the forensic medical departments of the regional bureaus of forensic medical examinations of Ukraine in this discipline has certain specific features.